Economic transition, dualism, and informality in India - Surbhi Kesar (University of Massachusetts, Department of Economics, 2019)
In much of the literature on economic development, sustained economic growth is expected to be accompanied by several interrelated processes of structure change, which involve a shift in economic activities from "traditional"/agricultural/informal to "modern"/industrial/formal sectors. Such transitions are usually accompanied by a transition in the economic dependence of households towards relatively "modern" and formal segments of the economy, along with a rise in their general economic well-being. In this paper, we examine the Indian economy using the only available household-level pan-India panel data over the high growth period between 2005 and 2011-12, to analyse the patterns and natures of household-level transitions across sectors and identify factors that affected the likelihood and nature of such transitions. We categorize households based on their primary income sources into seven sectors characterised by varying degrees of formality/informality and various production structures and labour processes. We find that while substantial proportion of households have transitioned across these sectors during the period, there has been a continued reproduction of the same economic structure, including a regeneration of dependence on "traditional" informal sector and casual wage employment, which are often expected to dissolve over time with high economic growth. To ascertain the nature of these transitions ("favorable" or "unfavorable"), we employ a "counterfactual" analysis. Contrary to some recent influential literature, we find that, on an average, the transitions towards informal and "traditional" economic spaces are "unfavourable" in nature in terms of well-being of households. Further, using a multinomial logit regression framework, we find that the likelihood and nature of these transitions are largely dependent on household characteristics like levels of education and social caste, some of which are structurally given and cannot be optimally chosen by households. The results show that despite significant churning in the economy, the structure continues to remain fractured, with substantial "unfavourable" transitions towards economic spaces that are continuously reshuffled and reconstituted.
Keywords: O17; J60; J46; O10; 330; structural transformation; informality; transition; segmentation; dualism; India